Milestone Sistem Perniagaan Karet di Rimbo Bujang Rentang Tahun 1980-2020 - Riyadi, Sugeng (Mabsya: Jurnal Manajemen Bisnis Syariah, 2021)
Processed rubber material (bokar) is a commodity that has been the mainstay of the Indonesian government. In order to realize the hegemony of production, the government organizes a transmigration program. This is at the same time to overcome the population problem on the island of Java. This qualitative type of research was carried out using the Bogdan and Taylor field approach using time series data. Patton's data analysis process, presented with manageable data. The data interpretation uses ideal types, path dependency and contingency strategies and Neuman's domain analysis. Research in Rimbo Bujang, in the 1980-2020 period, shows that the rubber trading system in the ex-transmigration sites of Jambi Province can be classified into three phases: first, trade between transmigrant farmers and the government. Second, farmers trade with cooperatives and middlemen. Third, farmers trade with middlemen using an auction pattern. Although the transmigration program in Rimbo Bujang was successful, it still left socio-economic problems, triggered by the trade system which tends to ignore Islamic economic principles. Findings in the field indicate that the absence of the state in plantation smallholder commerce contributes to the moral hazard of market participants. The change of plantation varieties from rubber to oil palm in the last decade does not rule out the possibility of repeating the previous cycle of rubber trading patterns.